Antibiotic exposure in hospitalized pediatric patients in the United States: prevalence and length of stay. Issue 11 (1st November 2020) - Gourishankar, Anand; Agbasi, Angela; Kain, Courtney; Lin, Ellen
ABSTRACT: Background: Hospital antibiotic use is rising. We aimed to evaluate the antibiotic-use prevalence and length of stay. Methods: We conducted a single-center retrospective study of patients < 18-years-old admitted to general pediatric services who received ≥ 1 antibiotic over six months. Demographics, culture results and antibiotic details were collected. The primary outcome was to identify the total number and classes of antibiotics prescribed during the admission. Secondary outcomes included length of stay (LOS), culture results, and the most commonly used antibiotics. Results: Forty-eight percent of patients received monotherapy (single class antibiotic). Cephalosporins (55%), vancomycin (35%), and clindamycin (22%) were prescribed more commonly than other antibiotic classes. Children were exposed up to 4 classes of antibiotics (range 1–4). A moderate correlation existed between the length of stay and the number of antibiotic classes used (R 2  = 0.38). Two or more classes of antibiotic use prolonged the length of stay. Cephalosporin use was associated with 35% reduced LOS (95 CI, 21%-57%), and penicillin use correlated with 38% more prolonged LOS (95 CI, 22%-66%). Conclusions: Antibiotic use in pediatric hospitals was high, and children received multiple classes of antibiotics. Inappropriate antibiotic use and culture results may have an untoward effect on hospital length of stay.